Biochemical and structural insights into an Fe(II)/α-ketoglutarate/O(2) dependent dioxygenase, Kdo 3-hydroxylase (KdoO) - Joo, Sang Hoon (J Mol Biol, 2018)
During lipopolysaccharide (LPS) biosynthesis in several pathogens, including Burkholderia and Yersinia, 3-deoxy-D-manno-oct-2-ulosonic acid (Kdo) 3-hydroxylase, otherwise referred to as KdoO, converts Kdo to D-glycero-D-talo-oct-2-ulosonic acid (Ko) in an Fe(II)/α-ketoglutarate(α-KG)/O(2)-dependent manner. This conversion renders the bacterial outer-membrane more stable and resistant to stresses such as an acidic environment. KdoO is a membrane-associated, deoxy-sugar hydroxylase that does not show significant sequence identity with any known enzymes and its structural information has not been previously reported. Here, we report the biochemical and structural characterization of KdoO, Minf_1012 (Kdo(MI)), from Methylacidiphilum infernorum V4. The De novo structure of Kdo(MI) apoprotein indicates that KdoO(MI) consists of 13 α helices and 11 β strands, and has the jelly roll fold containing a metal binding motif, HXDX(111)H. Structures of Kdo(MI) bound to Co(II), Kdo(MI) bound to α-KG and Fe(III), and Kdo(MI) bound to succinate and Fe(III), in addition to mutagenesis analysis, indicate that His146, His260, and Asp148 play critical roles in Fe(II) binding, while Arg127, Arg162, Arg174, and Trp176 stabilize α-KG. It was also observed that His225 is adjacent to the active site and plays an important role in the catalysis of KdoO(MI) without affecting substrate binding, possibly being involved in oxygen activation. The crystal structure of KdoO(MI) is the first completed structure of a deoxy-sugar hydroxylase, and the data presented here have provided mechanistic insights into deoxy-sugar hydroxylase, KdoO and LPS biosynthesis.